Himpunan keputusan Menteri Dalam Negeri/Ketua Lembaga Pemilihan Umum menghadapi pendaftaran pemilih/jumlah penduduk dan pencalonan (Lembaga Pemilihan Umum, 1981)
Decisions of the Minister of Home Affairs as head of the Indonesian General Elections Institute relating to voting administration and procedures for the 1982 elections.